2019
DOI: 10.1002/jcp.28424
|View full text |Cite
|
Sign up to set email alerts
|

miR‐144‐3p facilitates nasopharyngeal carcinoma via crosstalk with PTEN

Abstract: Aims This study aims to investigate the role of miR‐144‐3p and phosphatase and tensin homolog (PTEN) in nasopharyngeal carcinoma (NPC), along with their crosstalk with the phosphoinositide 3‐kinase (PI3K)–protein kinase B (Akt) pathway. Methods Quantitative reverse transcription polymerase chain reaction and western blot were used to measure the gene expression at the transcriptional and translational levels. 3‐(4,5‐Dimethylthiazol‐2‐yl)‐2,5‐diphenyltetrazolium bromide assay and colony formation assay were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…MiRNAs contained in MSC-derived exosomes could functionally inhibit PTEN expression, thereby activating PI3K/AKT signaling with subsequent inhibition of apoptotic injury and death in hypoxic CMCs [36,37]. To date, many studies [18][19][20]38] have confirmed PTEN as a miR-144 target. Bioinformatics analysis using TargetScan and miRTarBase has also confirmed that PTEN is a good candidate miR-144 target.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiRNAs contained in MSC-derived exosomes could functionally inhibit PTEN expression, thereby activating PI3K/AKT signaling with subsequent inhibition of apoptotic injury and death in hypoxic CMCs [36,37]. To date, many studies [18][19][20]38] have confirmed PTEN as a miR-144 target. Bioinformatics analysis using TargetScan and miRTarBase has also confirmed that PTEN is a good candidate miR-144 target.…”
Section: Discussionmentioning
confidence: 99%
“…MSC-derived exosomes can protect the heart from ischemia by increasing the level of miR-21a-5p in recipient cardiac cells, thereby downregulating expression of the pro-apoptotic gene phosphatase and tensin homolog deleted on chromosome 10 (PTEN) in the myocardium [7]. PTEN has been confirmed as a direct target of miR-144 [18][19][20], and miR-144 inhibited cell apoptosis through inhibition of PTEN and subsequent activation of the phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT) signaling pathway [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, miR-144 plays an oncogenic role in nasopharyngeal carcinoma and clear cell renal cell carcinoma. In these cancers, some established tumor suppressive genes were found to be the direct targets of miR-144, such as PTEN in nasopharyngeal carcinoma (Song et al, 2019), and ARID1A in clear cell renal cell carcinoma (Xiao et al, 2017). In prostate cancer, miR-144 was shown to enhance radiotherapy sensitivity and suppress hypoxia-induced autophagy by inhibiting PIM1 expression (Gu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…MiR-144 plays an oncogenic role in NPC tumorigenesis. Zhang et al and Song et al reported that the upregulation of miR-144 by the downregulation of tumor suppressor gene phosphatase and tensin homolog (PTEN) mediates cell proliferation, invasion, and metastasis in NPC specimens and cell lines [156,157]. Moreover, the downregulation of miR-144 by triptolide leads to an increase in p85α-PTEN complex and it causes cell cycle arresting in S-phase in human NPC cells [158].…”
Section: Mir-144 In Nasopharyngeal Carcinomamentioning
confidence: 99%